Strategi Tim Kreatif Nusantara TV Dalam Tayangan Jelajah Rasa Untuk Menarik Minat Penonton: indonesia - Sirait, Rusi Erika; Wulandari, Yulianti Fajar; Himawan, Sultan (Prisani Cendekia Institute, 2024)
Nusantara TV is a semi-national digital television network with national reach and based on private broadcasters, Nusantara TV has a variety of programs that are meaningful and informative for the community. One of the programs is Jelajah Rasa. The success of a television program cannot be separated from the role of the creative team that plays an important role in making the program. This research was conducted to find out how the creative team's strategy in Jelajah Rasa to attract viewers. This research method uses descriptive qualitative methods and Lasswell's mass communication theory with data collection techniques through in-depth interviews and observation. Based on the results of this study, it is known that determining targets, selecting airtime, determining ideas and themes, presenting styles, segment organization, maintaining image quality and evaluation are strategies used by the creative team to attract viewers.